Influence of Consumer Attributions and Service Quality on Support of Corporate Social Responsibility - Engizek, Nil; Yaşin, Bahar (Organizations and Markets in Emerging Economies, 2018)
This study examines whether or not a consumer will support a firm due to its CSR activities depending on what perceived motivation (egoistic, strategic, stakeholder and value driven attributions) the consumer has towards those activities and also analyzes how the relationship between consumers’ attributions and the change in their supportive behaviour according to their perceived service quality. The survey was conducted with customers of mobile telecommunication services in Turkey. In order to collect data to test the hypotheses, in accordance with the theory of stated preferences versus theory of revealed preferences, a face-to-face survey was carried out by adopting a quota sampling technique based on the market share of each mobile service provider. The sample consisted of 400 respondents who were drawn from the Istanbul metropolitan area. The results show that value driven, strategic  and stakeholder driven motives have a direct and positive effect. Egoistic  motive was found to be significant and had a negative effect. Service quality moderated only the relationship between strategy driven motives and supportive behaviour, and value driven motives and supportive behaviour, but in an unexpected direction.